2014
DOI: 10.1088/1748-9326/9/1/014008
|View full text |Cite
|
Sign up to set email alerts
|

Growing threat of intense tropical cyclones to East Asia over the period 1977–2010

Abstract: The threat of intense tropical cyclones (TCs) to East Asia has increased in recent decades. Integrated analyses of five available TC data sets for the period 1977-2010 revealed that the growing threat of TCs primarily results from the significant shift that the spatial positions of the maximum intensity of TCs moved closer to East Asian coastlines from Vietnam to Japan. This shift incurs a robust increase in landfall intensity over east China, Korea and Japan. In contrast, an increase of TC genesis frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 44 publications
7
82
1
Order By: Relevance
“…An upward trend in the proportion of intense typhoons (categories 4 and 5 on the Saffir-Simpson scale) in the western North Pacific basin since the late 1970s has been reported in the literature (Elsner et al, 2008;Kossin et al, 2007;Mei et al, 2015;Webster et al, 2005;Wu & Wang, 2008;Wu & Zhao, 2012). The intense typhoons that made landfall in the East Asia increased (Mei & Xie, 2016;Park et al, 2011Park et al, , 2014. Although the maximum potential intensity (MPI) theory (Emanuel, 1987;Holland, 1997) and numerical modeling (Bender et al, 2010;Knutson et al, 1998;Knutson et al, 2013;Knutson & Tuleya, 2004;Oouchi et al, 2006) consistently project an intensity increase of tropical cyclones in a warming climate, the factors responsible for the increasing trend have not been convincingly identified.…”
Section: Introductionmentioning
confidence: 81%
“…An upward trend in the proportion of intense typhoons (categories 4 and 5 on the Saffir-Simpson scale) in the western North Pacific basin since the late 1970s has been reported in the literature (Elsner et al, 2008;Kossin et al, 2007;Mei et al, 2015;Webster et al, 2005;Wu & Wang, 2008;Wu & Zhao, 2012). The intense typhoons that made landfall in the East Asia increased (Mei & Xie, 2016;Park et al, 2011Park et al, , 2014. Although the maximum potential intensity (MPI) theory (Emanuel, 1987;Holland, 1997) and numerical modeling (Bender et al, 2010;Knutson et al, 1998;Knutson et al, 2013;Knutson & Tuleya, 2004;Oouchi et al, 2006) consistently project an intensity increase of tropical cyclones in a warming climate, the factors responsible for the increasing trend have not been convincingly identified.…”
Section: Introductionmentioning
confidence: 81%
“…The observed regional shifts in TC activity in the WNP basin in recent decades may have significant implication for landfalling TCs and associated impacts various countries in the WNP . Further studies are required to identify the possible causes and relative contribution of global climate change to these changes.…”
Section: Research Topics For the Futurementioning
confidence: 99%
“…87,88 The observed regional shifts in TC activity in the WNP basin in recent decades may have significant implication for landfalling TCs and associated impacts various countries in the WNP. 197,198 Further studies are required to identify the possible causes and relative contribution of global climate change to these changes. Similarly, while climate models project more precipitation from TCs in the WNP (and globally) in the 21st century, observational studies and model simulations are required to assess the long-term variations of the total and extreme rainfall induced by TCs for different countries in the WNP (and globally) in the past and the 21st century.…”
Section: Confidence In Detection and Attribution Of Observed Changes mentioning
confidence: 99%
“…Anthropogenic contributions to TC track changes have been reported (Colbert et al 2013;Park et al 2014;Kossin et al 2016). Also, it has been shown that interdecadal changes of TC tracks in the western North Pacific are associated with the 5 westward expansion of the subtropical northwestern Pacific high (Ho et al 2004).…”
Section: Summary and Disucssionmentioning
confidence: 99%